The economics of rotating savings and credit associations: evidence from the Jamaican 'Partner' - Handa, Sudhanshu; Kirton, Claremont (Elsevier, 1999)
Using a unique sample of rotating savings and credit association (Rosca) members from Jamaica, we provide the first econometric tests of the recent theoretical advances in the literature on Roscas, and find considerable support for an economic theory of Roscas. We find, for example, that payments to the Rosca leader significantly enhance the sustainability of the Rosca, and that the contractual relationship between the leader and other Rosca members is transaction cost minimizing' when the degree of asset specificity is higher the contract is more flexible. Other theoretical predictions we validate are the inverse relationship between size of Rosca and size of contribution, and the use of Rosca funds for durable goods purchase.